2020
DOI: 10.4314/gmj.v54i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Vascularised fibular graft in the management of non-union of fracture shaft of radius: a less ventured entity

Abstract: Introduction: Non-union of the radius and ulna is a major complication of forearm fractures, accounting upto 10% of all forearm fractures. Multiple modalities are available for the treatment of non-union. Vascular grafts are a less sought-after surgical choice owing to the need of expertise and skills of surgeons. We discuss a case of gap non-union of fracture shaft radius treated with vascular fibula graft. Case Report: We describe a case of 45yr old lady with closed fracture of both bones of left forea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…With regard to the size of bone defects in osseous discontinuities, in animal populations, defects that do not heal spontaneously are critical size defects and complete defects of bone without the addition or induction of recruitment factors; 43 In humans, the definition of critical size is controversial and, depending on the nature of the injury causing the osteonecrosis and the individual patient, defects greater than 2.5 cm are generally considered to require surgical intervention and planned reconstruction. 44 In defects greater than 6-8 cm in length, bone grafts with anastomotic vessels offer significant advantages, 45 Other studies have also shown that anastomotic bone grafts with blood vessels are a valuable option for treating bone gaps greater than 6 cm. 46 In terms of the types of grafts available, there are dozens of vascularised bone grafts available for cutting throughout the body, such as fibula, ilium and scapula.…”
Section: Bone Graft With Anastomotic Vesselsmentioning
confidence: 99%
“…With regard to the size of bone defects in osseous discontinuities, in animal populations, defects that do not heal spontaneously are critical size defects and complete defects of bone without the addition or induction of recruitment factors; 43 In humans, the definition of critical size is controversial and, depending on the nature of the injury causing the osteonecrosis and the individual patient, defects greater than 2.5 cm are generally considered to require surgical intervention and planned reconstruction. 44 In defects greater than 6-8 cm in length, bone grafts with anastomotic vessels offer significant advantages, 45 Other studies have also shown that anastomotic bone grafts with blood vessels are a valuable option for treating bone gaps greater than 6 cm. 46 In terms of the types of grafts available, there are dozens of vascularised bone grafts available for cutting throughout the body, such as fibula, ilium and scapula.…”
Section: Bone Graft With Anastomotic Vesselsmentioning
confidence: 99%